Creation of distance courses in natural sciences for international students of preparatory phase of training in Ukrainian, Russian, English languages - O. M. Lapuzina; L. M. Lisachuk (Academy of Cognitive and Natural Sciences, 2017)
The aim of this study is to design and implement the educational learning environment for international students' studying in Ukrainian universities in the form of distance learning courses based on Moodle system. Objectives of the study is to analyze the existing approaches to constructing distance learning courses of training requirements in preparatory phase for foreigners in order to form a remote environment, experimental use of distance learning courses for foreigners in form of blended and distance learning during their preparation for entering universities in Ukraine. The object of research is the process of functioning of blended and distance learning for foreigners who plan to study in Ukrainian universities in Ukraine, Russian, Ukraine and English languages. The subject of research is the use of blended and distance learning for foreigners in organizational, scientific and educational activities of the Department of Natural Sciences of the Faculty of International Education of NTU "KhPI". In the work the analysis and systematization of research on the use of cloud-based ICT in education, research and organizational activities of the university, experimental implementation of the designed cloud-based environment for the subdivision of university using open source software. To assess the effectiveness of the use cloud-based learning environment created a separate department university planned to hold teaching experiment. In this work the analysis and systematization of use the blended and distance learning for foreign citizens in educational process was made, and the experimental introduction of advertising-course "Welcome to study!" developed on the basis of Moodle system in the distance learning courses NTU "KhPI" was fulfilled. To assess the efficiency of distance learning courses for international citizens' preparatory phase of training according to the basic natural sciences, the pedagogical experiment will be done. Results of the study is planned to summarize the development of recommendations for the design of distance learning courses for foreigners with special courses for distance or blended learning in universities Ukraine.